Spiritual capital - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
This program explores the principles and values that we often equate with spirituality and what these values are worth to our society. When it comes to worldly wealth, some say: 2You can't take it with you.3 But some scholars and researchers we've spoken to believe that there is a wealth that does live on. They believe YOU CAN take it with you. Join us to explore this topic.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Spiritual life